Virtuosité d’une sphère en mouvement - Stéphane Rennesson (Ateliers d'Anthropologie)
The controversy over individual risk, uncalled technical gesture, unfortunate technical  ornament that can ruin everything, often have the effect of enclosing football in a simplistic point of view concerning the articulation of individual and collective action in general. In football, are we necessarily doomed to oscillate between the individual and the collective? If football seems imbued with virtuosity, a problem arises when it must be attributed and isolated in actions that are often muddled. On the basis of technical actions performed by famous dribblers, this paper shows that the movement of the ball on a field is not explained by the technical virtuosity of a single individual, nor simply by the result of the sum of individual actions, let alone by just the product of a tactical plan. While moving, the ball is charged and discharged of effects depending on the relations between the players on the field. The "ball in movement", this generator of actions, will require us to go towards physics and to try a slightly shifted form of game commentary. Recognition of the physical potential of the ball, which is multiplied by the number of times it is touched, is a prerequisite before any analysis of football virtuosity and its modes of expression.